Pengembangan Media dan Pelatihan Pembuatan Telur Asin dari Telur Ayam sebagai Upaya Melatih Jiwa Entrepreneur pada Siswa SDN Gadingsari - Muhammad Andi Saputra; Shafa Eka Septiani; Brimastiar Hartanto; Salsabila Zahwa Maulid; Habbil Backtian Armansyah; Verdyansah Anang Prasetyo; Roni Yulianto; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This social project aims to strengthen entrepreneurial skills among elementary school students through the development of practical learning media and hands-on training in producing salted eggs using chicken eggs. A total of 19 students from SDN Gadingsari participated in a four-week program involving lectures, demonstrations, direct practice, and basic guidance in packaging and simple marketing. The evaluation involved pre-tests, post-tests, observations, and satisfaction questionnaires. Results indicated an 18.5% increase in students' knowledge, with average scores rising from 65 to 77. Additionally, 85% of students expressed increased confidence and motivation to apply the skills learned, while 70% successfully practiced salted egg production at home. These outcomes demonstrate that the program effectively enhanced students' understanding, practical abilities, and entrepreneurial mindset, supporting the development of independence and creativity at the elementary school level.